Salts and salt cocrystals of the antibacterial drug pefloxacin - Gunnam, Anilkumar; Suresh, Kuthuru; Nangia, Ashwini (Crystal Growth & Design, 2018)
Pefloxacin (PEF) is an amphoteric, antibacterial drug which exists as a neutral molecule in the crystal structure stabilized by C-H center dot center dot center dot O and C-H center dot center dot center dot F interactions. The design of multicomponent solids using crystal engineering was undertaken in a cocrystal/salt screen of PEF with generally recognized as safe (GRAS) dicarboxylic acids to improve the solubility and phase stability of the drug. Ten multicomponent forms, namely, five salts, two salt hydrates, and three salt cocrystals, were prepared by liquid-assisted grinding followed by crystallization. In some cases, salt and salt cocrystals were obtained concomitantly during solution evaporative crystallization. Single crystal X-ray diffraction showed that the structures are stabilized by N+-H center dot center dot center dot O-, O-H center dot center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot F, and pi-pi stacking interactions. The bulk phase purity of multicomponent forms was characterized by powder X-ray diffraction, spectroscopy, and thermal techniques. The salt/salt cocrystal forms exhibit a faster dissolution rate and higher solubility compared to pure PEF in pH 1.2 (acidic, like gastric environment) and pH 7 phosphate buffer media (neutral, like intestinal passage). Specifically the PEF+-SA(-) salt (SA = succinic acid) showed remarkably high solubility, dissolution rate, and stability compared to the other multicomponent forms and PEF neutral form. The drug formulation compatible pefloxacin succinate is a promising soluble and stable PEF salt.